2008
DOI: 10.1159/000149835
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intraoperative Measurement of Parathyroid Hormone in Parathyroid Surgery

Abstract: Technological developments have significantly contributed to the rapid evolution of the surgical management of parathyroid disorders. The ability to physiologically determine the intraoperative status of the patient is now possible through the assessment of changing levels of intact parathyroid hormone (PTH) during surgery. In most patients with primary hyperparathyroidism, this method provides biochemical confirmation of hyperfunctional gland removal, and is predictive of a eucalcemic state and surgical cure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 146 publications
1
3
0
2
Order By: Relevance
“…Our review of our series of eight consecutive patients demonstrated a 100% cure rate in both surgical approaches. This is comparable to data showing that the surgical cure rate after MIP is comparable with CNE (14,15) Our results demonstrate the advantages of IOPTH-guided minimally invasive parathyroidectomy (8).…”
Section: Discussionsupporting
confidence: 88%
“…Our review of our series of eight consecutive patients demonstrated a 100% cure rate in both surgical approaches. This is comparable to data showing that the surgical cure rate after MIP is comparable with CNE (14,15) Our results demonstrate the advantages of IOPTH-guided minimally invasive parathyroidectomy (8).…”
Section: Discussionsupporting
confidence: 88%
“…[ 35 ] Many other studies show results which are consistent with our study. [ 36 37 38 39 40 41 42 ]…”
Section: Discussionmentioning
confidence: 99%
“…Darüber hinaus konnte nachgewiesen werden, dass das Morbiditätsspektrum von Osteoporo se, Knochenschmerz, Nephrolithiasis, ein geschränkter Nierenfunktion, Gastrointes tinalulzera, Pankreatitis, Obstipation, ar terioskleroseassoziierten Affektionen des HerzKreislaufSystems, mnestischen Stö rungen sowie Ermüdbarkeit und Energie verlust durch die erfolgreiche Operation günstig beeinflusst wird [2,18,24,29].…”
Section: Intraoperative Parathormonbestimmung Beim Primären Hyperparaunclassified
“…Nachweis eines von zervikal nicht erreichbaren me diastinal gelegenen NSDFokus, der heute in vielen Fällen durch thorakoskopischen Zugang ohne Sternotomie erreicht und beseitigt werden kann [24]. Gerade beim Rezidiveingriff eines PHPT kommt be züglich der Frage der IOPTHBestim mung das Argument zum Tragen, nach Entfernung des fraglich hyperaktiven Ne benschilddrüsengewebes Sicherheit zu er langen, dass keine weitere Quelle hyper aktiven NSDGewebes vorliegt.…”
Section: > Die Entwicklung Eines Späteren Phpt-rezidivs Kann Nicht Auunclassified